The endothelin receptor antagonist macitentan ameliorates endothelin-mediated vasoconstriction and promotes the survival of retinal ganglion cells in rats - Kodati, Bindu; Zhang, Wei; He, Shaoqing; Pham, Jennifer H.; Beall, Kallen J.; Swanger, Zoe E.; Krishnamoorthy, Vignesh R.; Harris, Payton E.; Hall, Trent; Tran, Ashley V.; Chaphalkar, Renuka M.; Chavala, Sai H.; et al. (Frontiers in Ophthalmology, 2023)
Glaucoma is a chronic and progressive eye disease, commonly associated with elevated intraocular pressure (IOP) and characterized by optic nerve degeneration, cupping of the optic disc, and loss of retinal ganglion cells (RGCs). The pathological changes in glaucoma are triggered by multiple mechanisms and both mechanical effects and vascular factors are thought to contribute to the etiology of glaucoma. Various studies have shown that endothelin-1 (ET-1), a vasoactive peptide, acting through its G protein coupled receptors, ETA and ETB, plays a pathophysiologic role in glaucoma. However, the mechanisms by which ET-1 contribute to neurodegeneration remain to be completely understood. Our laboratory and others demonstrated that macitentan (MAC), a pan endothelin receptor antagonist, has neuroprotective effects in rodent models of IOP elevation. The current study aimed to determine if oral administration of a dual endothelin antagonist, macitentan, could promote neuroprotection in an acute model of intravitreal administration of ET-1. We demonstrate that vasoconstriction following the intravitreal administration of ET-1 was attenuated by dietary administration of the ETA/ETB dual receptor antagonist, macitentan (5 mg/kg body weight) in retired breeder Brown Norway rats. ET-1 intravitreal injection produced a 40% loss of RGCs, which was significantly lower in macitentan-treated rats. We also evaluated the expression levels of glial fibrillary acidic protein (GFAP) at 24 h and 7 days post intravitreal administration of ET-1 in Brown Norway rats as well as following ET-1 treatment in cultured human optic nerve head astrocytes. We observed that at the 24 h time point the expression levels of GFAP was upregulated (indicative of glial activation) following intravitreal ET-1 administration in both retina and optic nerve head regions. However, following macitentan administration for 7 days after intravitreal ET-1 administration, we observed an upregulation of GFAP expression, compared to untreated rats injected intravitreally with ET-1 alone. Macitentan treatment in ET-1 administered rats showed protection of RGC somas but was not able to preserve axonal integrity and functionality. The endothelin receptor antagonist, macitentan, has neuroprotective effects in the retinas of Brown Norway rats acting through different mechanisms, including enhancement of RGC survival and reduction of ET-1 mediated vasoconstriction.